Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Pasien Pada Bagian Pendaftaran Rawat Jalan Di RSUD Cilincing Tahun 2023 - Novia Chilfi; Herudini Subariyanti (Prisani Cendekia, 2023)
According to the Indonesian Ministry of Health Regulation Number 129 of 2008 regarding the minimum service standards for hospitals, the patient satisfaction with services should reach 100%. However, the actual situation in the field indicates a different reality. There are issues with service quality in Indonesia. Data shows fluctuations in the number of outpatient visits every month. In the past year, a total of 87,304 patients visited, with 75,642 being returning patients and 11,341 being new patients. The most significant drop in patient visits occurred from February to March. This study aims to examine and analyze the Influence of Service Quality and Facilities on Patient Satisfaction in the Outpatient Registration Department at RSUD Cilincing. In this research, the independent variables are service quality and facilities, while the dependent variable is patient satisfaction. The research methodology includes tests for normality, multicollinearity, heteroskedasticity, correlation coefficients, Multiple Regression Analysis, t-tests, and F-tests. The results of the study indicate that the variable